Climate-Related Disasters in Asia and the Pacific - Vinod Thomas; Jose Ramon G. Albert; Rosa T. Perez (Asian Development Bank (ADB), 2013)
Natural disasters are on the rise worldwide. There are more and more intense natural disasters - which are defined to cause at least 100 deaths or to affect the basic survival needs of at least 1,000 people - resulting from floods and storms as well as droughts and heat waves. The Asia and the Pacific region has experienced some of the most damaging disasters in recent decades, with alarming consequences for human welfare. At the same time, the climate in the region has been changing. Temperatures have been higher, on average, and also more variable and more extreme. Rainfall has also been more variable and more extreme. Is there a relationship between these changes in climate and the increase in natural disasters in Asia and the Pacific? This paper considers three main disaster risk factors - rising population exposure, greater population vulnerability, and increasing climate-related hazards - behind the increased frequency of intense natural disasters. In a regression analysis within a model of disaster risk determination, the most significant association is between the increase in natural disasters and population exposure, represented by population densities. Population vulnerability also matters, but increasing incomes seem to be associated first with greater and then lesser vulnerability. Finally, there is a notable association between climate-related hazards (greater precipitation linked to floods and storms and especially higher temperature linked to droughts and heat waves) and the frequency of intense natural disasters in Asia and the Pacific and its subregions during 1971–2010. Along with the scientific association between greenhouse gases and the changes in the climate, the findings in this paper suggest that there is a link between increasing natural disasters in Asia and the Pacific and man-made emissions of greenhouse gases in the atmosphere.
hdl:11540/2311
Keywords: C23; Q54; Q56; Q58; 330; natural disasters; intense disaster climate change; hazard; exposure; vulnerability; precipitation; temperature; tropical cyclone; typhoon; Philippines